A study on swimming pool maintenance at condominium / Mohamad Faizal Abdul Aziz - Abdul Aziz, Mohamad Faizal (2009)
In recent years, more Malaysians are moving into stratified unit, especially in urban centers due to limited land availability. Thus, the developer designs the high rise condominium completely with their additional facilities such as swimming pool. Maintenance management of the condominium should properly maintain the swimming pool because swimming pool water easy to become cloudy and other systom. However, with the increasing development of strata titled property and legislation to govern the property management of such property, there has been an increasing demand for professional property management skills. Therefore, this study has been developed with the aim to analyze the cost of swimming pool in condominium and the scope of the study is surrounding Shah Alam. The study was conducted through structured interview to the maintenance department of the condominium. From the study, it was found the maintenance and associated operation cost in swimming pool maintenance which it finding found the element that contribute a lot of cost in maintenance and operation. The first element is electricity and another one is chemical. The percentage allocate to the swimming pool maintenance more effected the total cost of maintenance work.